2000
DOI: 10.1046/j.1439-0329.2000.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the management of a Picea abies stand under risk of butt rot

Abstract: A simulation model was developed to predict the growth of a Norway spruce stand under risk of butt rot caused by Heterobasidion annosum stump infection and logging injuries. The simulation model was distance-dependent; tree growth was predicted with a distance-dependent model, and the spread of butt rot through root contacts depended on tree location. Infection of stumps and injured trees, and the spread of butt rot in the stand were stochastic processes whereas tree growth and mortality were treated as determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Valsta 1992a, 1992b, Möykkynen et al 2000, Pukkala and Miina 2005. In the other fields a new type of methods, called as population-based methods or evolutionary computation methods, have also been used to solve complicated optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…Valsta 1992a, 1992b, Möykkynen et al 2000, Pukkala and Miina 2005. In the other fields a new type of methods, called as population-based methods or evolutionary computation methods, have also been used to solve complicated optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…The method has also been employed to solve the optimisation problem when risk is involved (Thorsen and Helles 1998, Möykkynen et al 2000, in spatial thinning problems (Pukkala and Miina 1998) and to optimise the management of agroforestry systems (Muchiri et al 2002). These examples showed that Hooke and Jeeves´algorithm is an interesting and reliable technique to be applied in optimization at the stand level.…”
Section: Methods Of Hooke and Jeevesmentioning
confidence: 99%
“…Rotation length has been the only decision variable and the risk of fire has been assumed to be age-dependent (Martell 1980), constant over time (Routledge 1980) or a time-independent Poisson process (Reed 1984). Some years ago, thinnings have been integrated in optimisations problems that include risks (Thorsen and Helles 1998, Möykkynen et al 2000, Amacher et al 2005a, González-Olabarría et al 2008.…”
Section: Stand Level Optimisationmentioning
confidence: 99%
“…This technique is very popular because it is easy to use and can perform well with discreteness of growth models on the expected concavity of the response surface. The Hooke and Jeeves method is described as a Bdirect search method^, which involves a sequential examination of the changes that occur when a problem is solved and the results are compared to the Bbest^solution among the derived [25][26][27][28][29][30][31][32][33]. Generally, the Hooke-Jeeves algorithm consists of two major phases: an Bexploratory search^around the base point and a Bpattern search^in a direction selected for optimization (minimization or maximization) [16].…”
Section: Non-linear Programming (Nlp) Approachmentioning
confidence: 99%
“…Several researchers including Miina [82], Vettenranta and Miina [83], Miina and Pukkala [30], Möykkynen et al [29], Wikström and Eriksson [84], Wikström [46], Hyytiäinen and Tahvonen [85], and Ribeiro et al [74] tackled the thinning optimization problems with distance-dependent control variables for the growth simulator. Only Ribeiro et al [74] applied DP by MSPATH.…”
Section: General Formulation Of Forest Stand-level Planning Problemmentioning
confidence: 99%